(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
The concentration of radioisotopes, 228Ac, 212Bi, 214Bi, 214Pb, 212Pb of the natural radiation series was determined by the unit (Bq / kg). By using Gamma Rays Spectrometry, by using NaI(Tl) scintillation. The samples were collected from the areas of phosphate spread in the Syrian coast (Ain Lilon, Al-Muhallabah, Ain Al-Tineh). These results show that the highest value of the Activity concentration of Lead Pb-214 reached (167.40 Bq / kg) in the sample Al 2 in the Ain Lilon section, and for Lead Pb- 212 was (1671 Bq / kg) in the sample Al 2 in Ain Lilon section as well. The highest value of the Activity concentration of Bismuth Bi- 214 was (72.89 Bq/ kg) in the sample Al 2 at the Ain Lilon section, and and for the Bismuth Bi-212 was (1157 Bq / kg) in the sample Al 2 in the Ain Lilon section as well. The highest value of the Activity concentration of Actinium Ac- 228 was (1936 Bq / kg) in the Mh7 sample at the Muhallabah section. These results show an increase in Activity concentration in the areas of phosphate